Electric Machinery Fundamentals - Chapman, Stephen (Boston Mcgraw Hill Higher Education, 1999)
"Electric Machinery Fundamentals" continues to be a best-selling machinery text due to its accessible, student-friendly coverage of the important topics in the field. Chapman's clear writing persists in being one of the top features of the book. Although not a book on MATLAB, the use of MATLAB has been enhanced in the fourth edition. Additionally, many new problems have been added and remaining ones modified. "Electric Machinery Fundamentals" is also accompanied by a website the provides solutions for instructors, as well as source code, MATLAB tools, and links to important sites for students.